1996
DOI: 10.1099/13500872-142-3-611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nitrogen Source on Phycobiliprotein Synthesis and Cell Reserves in A Chromatically Adapting Filamentous Cyanobacterium

Abstract: Besides these differences in cell pigmentation, a rapid but transient accumulation of cyanophycin granule polypeptide occurred in ammoniumgrown cells, while these macromolecules were not detected in cells grown with nitrate. In contrast, glycogen reserves displayed a dynamic pattern of accumulation and disappearance during cell growth which varied only slightly with the nitrogen source. The observed changes in cell pigmentation are reminiscent of the phenomenon of complementary chromatic adaptation, in which g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 60 publications
(81 reference statements)
2
70
1
1
Order By: Relevance
“…Cyanobacteria are a diverse group of photosynthetic microorganisms with specific physiological and morphological characteristics that allow them to adapt to a wide range of habitats including pelagic and benthic environments where they are highly competitive (Liotenberg et al, 1996;Morvan et al, 1997;Oren, 2000). Some species can survive under extreme environmental conditions such as deserts, hot springs and alkaline lakes (Oren, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria are a diverse group of photosynthetic microorganisms with specific physiological and morphological characteristics that allow them to adapt to a wide range of habitats including pelagic and benthic environments where they are highly competitive (Liotenberg et al, 1996;Morvan et al, 1997;Oren, 2000). Some species can survive under extreme environmental conditions such as deserts, hot springs and alkaline lakes (Oren, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…most cyanobacteria as nitrogen, carbon, and energy storage compound in the early stationary growth phase (1,2). The water-insoluble CGP is accumulated intracellularly in the form of membraneless granules (3) and is degraded by the cells when growth is resumed.…”
mentioning
confidence: 99%
“…The correlations between nitrogen concentration and cells growth as well as on the pigment production were well documented. Nitrogen is an essential major element required for the synthesis of primary and secondary amino acids, proteins, nucleic acids, coenzymes, chlorophyll and other accessory photosynthetic pigment such as phycobiliproteins in cyanobacteria [5]. It was reported that the concentration of KNO 3 as nitrogen source was found to be an essential factor influencing the growth of Synechocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…In many papers, the effects of nutrient, light, pH, temperature and co-cultivation with competitive organisms on the synthesis of cyanobacterial metabolites were well documented [5][6][7]. It was expected that those factors might stimulate the production of OsPP.…”
Section: E3s Web Of Conferences 47mentioning
confidence: 99%
See 1 more Smart Citation